2021
DOI: 10.1186/s13000-021-01124-0
|View full text |Cite
|
Sign up to set email alerts
|

Central mucoepidermoid carcinoma arising directly from a glandular odontogenic cyst of the mandible: a case report

Abstract: Background Central mucoepidermoid carcinoma (MEC) is a rare salivary gland tumor that affects the jawbone. Glandular odontogenic cyst (GOC) is also a rare odontogenic developmental cyst with glandular differentiation. GOC shares some histological features with central MEC, and a pre-existing GOC can develop into central MEC. Here, we present a rare case of central MEC developed directly from a pre-existing GOC of the mandible. Case presentation A 6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…MAML2 rearrangement in MEC is not specific to salivary gland origin, as MEC of other origins, such as thymus, lung, lacrimal gland, and uterine cervix, have also demonstrated MAML2 rearrangement [25][26][27][28]. Our literature review only identified nine reports/studies documenting the presence of MAML2 rearrangement in CMEC in 30 cases (Table 1) [10][11][12][13][14][15][16][17][18]. Of these, site and demographic information are provided for 25 cases [10,11,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAML2 rearrangement in MEC is not specific to salivary gland origin, as MEC of other origins, such as thymus, lung, lacrimal gland, and uterine cervix, have also demonstrated MAML2 rearrangement [25][26][27][28]. Our literature review only identified nine reports/studies documenting the presence of MAML2 rearrangement in CMEC in 30 cases (Table 1) [10][11][12][13][14][15][16][17][18]. Of these, site and demographic information are provided for 25 cases [10,11,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review only identified nine reports/studies documenting the presence of MAML2 rearrangement in CMEC in 30 cases (Table 1) [10][11][12][13][14][15][16][17][18]. Of these, site and demographic information are provided for 25 cases [10,11,[13][14][15][16][17][18]. The mandible represents 64% of cases, with 36% occurring in the maxilla [10,11,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central MEC is a rare intraosseous variant occurring in the jaws and represents only 2% to 4% of all MECs 10,11 . It occurs most frequently in the fourth and fifth decade of life, with a male to female ratio of 1:1.45 12 ; in 50% of cases, they are associated with odontogenic cyst or unbroken tooth 13 …”
Section: Introductionmentioning
confidence: 99%
“…10,11 It occurs most frequently in the fourth and fifth decade of life, with a male to female ratio of 1:1.45 12 ; in 50% of cases, they are associated with odontogenic cyst or unbroken tooth. 13 Several theories regarding its origin have been postulated. [14][15][16][17] The most worthy considered neoplastic transformation of the epithelial lining of odontogenic cysts to be the most plausible in tumor's development.…”
Section: Introductionmentioning
confidence: 99%